Evaluasi Dampak Program Bantuan Sosial terhadap Pengentasan Kemiskinan di Wilayah Perdesaan - Ahmad Wahyudi Zein; Nurul Hikmah Pasaribu; Sukma Anggriani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research uses a qualitative method to evaluate the impact of social assistance programs on poverty alleviation in rural areas. The focus of this study is on how effectively the implementation of social assistance programs can improve the welfare of the rural poor, particularly in terms of economic conditions, social well-being, and quality of life. The findings indicate that social assistance programs have had a positive impact in reducing the economic burden of poor households, improving access to education and healthcare services, and encouraging community empowerment through productive economic activities. However, challenges remain, such as mistargeted beneficiaries, delays in distribution, and lack of supervision in program implementation. Therefore, continuous evaluation and active involvement from all stakeholders, including local governments and rural communities, are needed to ensure the optimal achievement of poverty alleviation goals. This study also recommends improvements in data collection systems and monitoring to ensure that social assistance programs are more effective and sustainable in the future.